Behavioral Tactics to Drive Spending and Prolong Play in the Video Game Industry - Aruťuňan, David; Sigmund, Tomáš; Pavlů, David; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The video game industry’s monetization strategies have transformed from one-time purchases to dynamic “live service” models that leverage behavioral psychology and predatory techniques to drive ongoing player engagement and recurring spending. The main goal of this bachelor thesis is to consolidate research about these psychological methods and how they are used in the video game industry. The first part reviews key psychological techniques and describes how they are embedded in specific monetization models. The second part empirically analyzes player experience, gaming and spending habits, and awareness of these psychological methods through quantitative research. By consolidating fragmented literature and combining it with original empirical data, this paper provides a structured overview of how behavioral psychology is commodified in gaming. The findings offer actionable insights for players, game developers and regulators aiming to understand and ethically govern the psychological design tactics found in video games.
Vedoucí práce: Tomáš Sigmund
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses